2020
DOI: 10.1103/physrevb.102.115405
|View full text |Cite
|
Sign up to set email alerts
|

Understanding high-field electron transport properties and strain effects of monolayer transition metal dichalcogenides

Abstract: Monolayer transition metal dichalcogenides (MX2) are promising candidates for future electronics. Although the transport properties (e.g. mobility) at low electric field have been widely studied, there are limited studies on high-field properties, which are important for many applications. Particularly, there is lack of understanding of the physical origins underlying the property differences across different MX2. Here by combining first-principles calculations with Monte Carlo simulations, we study the high-f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Our result with a relatively moderate excitation fluence of approximately ten μJ/s cm –2 experimentally confirms that the energy renormalization effect can be effective even below the Mott threshold of 10s of meV, which is also reasonably supported by the theoretical prediction . This finding supports the potential valley-electronic applications of TMDs at the Q valley, such as the Mott transition, , Q valley TMD transistors, , and negative differential conductance. , …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our result with a relatively moderate excitation fluence of approximately ten μJ/s cm –2 experimentally confirms that the energy renormalization effect can be effective even below the Mott threshold of 10s of meV, which is also reasonably supported by the theoretical prediction . This finding supports the potential valley-electronic applications of TMDs at the Q valley, such as the Mott transition, , Q valley TMD transistors, , and negative differential conductance. , …”
Section: Discussionsupporting
confidence: 86%
“…In 2D TMDs, photoexcitation or hot carrier injection has provided a powerful tool to control the valley degree of freedom. , The excessive carriers confined in the layered structure of TMDs lead to considerable many-particle interactions. This many-body system, bringing the energy renormalization effect and shrinking the quasiparticle bandgap in the valley band structure at the K points, has been studied using optical technologies in the past decade. , Recently, another local minimum of the conduction band (CB) has been noted to lie midway between the K and Γ points, higher by a few meV than the K point, which is called the Q valley , and has been theoretically reported to strongly couple with the K valley on the CB edge. Intriguingly, the Q valley was theoretically predicted to be more sensitive to the energy renormalization effect than the K valley due to its differing orbital character and the nonsignificant hole population at the Q point . Therefore, the CB K - Q valley coupling will be dramatically strengthened under the energy renormalization effect with increased carriers, altering the electronic transport and optoelectronic properties in TMD devices. Thus, providing a complete understanding of the underlying physics and developing control of the electronic behavior at the Q valley become key to future valleytronic technologies.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Jin et al [44] show that WS 2 has a higher saturation velocity at fields > 100 kV cm −1 and it appears that there is no NDC behavior in their results. At the same time, in a study conducted by Zhang et al, it is shown that WS 2 has the highest peak velocity and the strongest NDC among MoS 2 , MoSe 2 , and WSe 2 [54].…”
Section: Introductionmentioning
confidence: 86%
“…The electron transport properties of WS 2 at high fields are investigated by several researchers [33,54,60] where they represented the velocity-field characteristics of the material, studied the relative electron populations of two valleys (K and Q valleys) as a function of applied electric field and reported on the negative differential conductance (NDC) phenomenon observed in experiments [33]. In addition, the same authors studied the effect of strain on the energy separation between K and Q valleys which is also investigated by [45,54,[60][61][62][63][64][65]. Ferry [60] found that MoS 2 has a higher saturation velocity than WS 2 at high fields and WS 2 begins to show NDC for ∆E KQ > 100 meV where ∆E KQ is the energy separation between the minima of K and Q valleys (see figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, one can first calculate the g for a sparse grid using DFPT, and then interpolate to the fine grid. Wannier interpolation using EPW software [27][28][29] can interpolate the short-range part of the g, while it misses some long-range parts including the 2D Fröhlich [16,30,31] and quadrupole interactions [32][33][34][35] that dominate the g with long phonon wavelength (i.e. small |q|).…”
Section: First-principles Computationsmentioning
confidence: 99%